Women's contributions to household food security in Oriire Local Government Area, Oyo State, Nigeria (2008)
Women's activities in Oriire Local Government Area, Oyo state were studied to determine their contributions to household security. The study used interview schedule to collect information from a total of 120 women, randomly selected from each of the 6 communities chosen out of 10. Data were analysed using frequency counts, chi-square and Pearson Product Moment Correlation statistics. Women studied were described as typically middle aged- mainly over 40 years of age (36.7%), married (92%), and have had one or more form of education or the other (80%). Majority of the women are responsible for children's school snack: (83.5%), medical bills (76.7), clothes (73.3), school books (70.8%) and uniforms (53.3%). Also they make farm produce available for household use (76.6%), feed the household (75.8%) and cook their meals (71.7%). Major concerns expressed by these women are inadequate capital base (47%), amenities (30.2%) and agricultural inputs (11.4%). Significant relationships exist between women's educational level and their contributions towards household food security (X2 = 20.7, P = 0.029). Also the women's income generating activities correlated positively with their contributions to household food security (r =0.274, p = 0.05). It is therefore pertinent to-establish agricultural-credit and training schemes that will improve these women's income generating capacities, knowledge base, and leadership skills to enable them make better choices in their production process as these will further enhance the food status of their households.